The Effect of Aesthetic Principles and a Functional Prime on Participant Ratings of Visual Appeal. (September 2018) - Kent, Travis M.; Carswell, C. Melody; Popham, Jamey
A recent thread of usability research is the investigation of the relationship between a product's degree of usability and its degree of beauty. Previous research endeavors have found support for both "what is beautiful is usable" and "what is usable is beautiful" claims, emphasizing the need for further study on the topic. The current study was performed to further investigate this relationship by manipulating usability indirectly – by use of a functional prime, and by experimentally manipulating aesthetic principles. One hundred twenty-two participants rated sixteen manipulated on four aesthetic principles: symmetry, composition, curvature, and prototypicality after being presented with one of two functional primes. Results indicate that the aesthetic principles of symmetry and composition are independent primed function whereas curvature was dependent on priming.